Becoming Active Citizens : Practices to Engage Students in Civic Education Across the Curriculum (an Innovative Resource Geared to Transform Civic Education in the Classroom). - Driscoll, Tom (Solution Tree, 2022)
"In Becoming Active Citizens: Practices to Engage Students in Civic Education Across the Curriculum, authors Tom Driscoll and Shawn W. McCusker provide educators with tools and strategies to reimagine civics education. Often, civics instruction in schools does not prepare or empower students to participate in civic discourse or other forms of civic engagement. Without high-quality civics education, students lack the skills and knowledge to participate in democracy, placing them at a disadvantage. The authors share practical strategies and technological resources to transform and reignite civics education. By reading Becoming Active Citizens, educators discover how to create authentic, engaging civics learning experiences for all students"--